Ralph Holloway (1935–2025): Pioneering paleoneurologist - Amélie Beaudet; Bernard Wood (Proceedings of the National Academy of Sciences, 2025)
Ralph Holloway pioneered and developed the field of hominin paleoneurology. Although Holloway’s undergraduate degrees were in metallurgical engineering and geology, at graduate school his interests switched to the brain. Holloway and his graduate students explored many aspects of the macro- and microstructure of the brain of extant primates but he focused on the recent evolutionary history of the human brain. The infant skull of the first African early hominin discovered at Taungs by Raymond Dart included a natural brain endocast. Natural endocasts as well-preserved as that of the Taungs infant are rare, but Holloway reasoned that if a way could be found to reproduce the endocranial morphology of early hominin crania then he would be able to track brain evolution within the human clade. Holloway realized that if liquid latex was introduced into the cranial cavity and left to cure, it could be extracted via the foramen magnum and then be used to make a facsimile of that individual’s brain. Modern imaging methods have made Holloway’s technique redundant, but for many years, it was the only way to access the endocranial morphology of fossil hominins.